Fatal hepatitis associated with diclofenac. Issue 11 (November 1986) - Breen, E G; McNicholl, J; Cosgrove, E; McCabe, J; Stevens, F M
Abstract : Non-steroidal anti-inflammatory agents (NSAIDS) are a well recognised cause of hepatotoxicity. Diclofenac, a relatively new NSAID, was first introduced into the UK in 1979. Five cases of hepatitis have recently been reported, principally in the French literature. We report the first fulminant case of hepatitis in the English literature in a patient taking diclofenac and indomethacin.